Implementasi Algorithma Dijkstra Dalam Pencarian Rute Terpendek Fasilitas Kesehatan Tingkat I (Studi Kasus BPJS Kesehatan Kota Bengkulu) - Wijaya, Ardi; Kurniawan, Edo (Jurnal Media Infotama, 2019)
Faskes is an abbreviation for health facility, while 1 is the first level, so health facility 1 means first level health facility and is the first place that participants must go to if they want treatment. If Health Facility 1 is unable both in terms of human resources and medical equipment, then participants will referred to a follow-up health facility. The Djikstra algorithm is named after its inventor, Edsger Djikstra. Djikstra's algorithm uses the greedy principle, where at each step the edge with the minimum weight is selected that connects a node that has been selected with another node that has not been selected [1]. Web application that can determine the shortest route so that it makes it easier for users to search for health facilities with the closest distance. The app uses Google Maps to display health facility location data, show routes to destinations, and more. To use Google Maps on this application. It is hoped that this application will always update data so that this application follows developments in GIS technology